Streptococcus Intermedius Lung Abscess in a 17-year-old Male - Levine, Jason Andrew; Hovsepyan, Karen; Lubarsky, Daniel; Mukundan, Deepa; Ruddy, Jennifer (Translation: The University of Toledo Journal of Medical Sciences, 2019)
Streptococcus intermedius lung abscess and empyema is a chronic infectious process associated with a high morbidity and mortality. It is typically seen in adults, and is considered a rare disease process in the pediatric population. Our case describes a 17 year old male presenting with 3 months of cough associated with later development of chest and back pain. He was later found to have a severe empyema secondary to Streptococcus intermedius. This case underlines a rare diagnosis in the pediatric population, as well as a association with smoking and vaping.